Personalized medicine and back–allogeneic exosomes for cancer immunotherapy. (29th August 2019) - Samuel, M.; Gabrielsson, S.
Abstract: Extracellular vesicles, especially exosomes, have been explored for cancer immunotherapy. The initial studies made use of autologous B‐cell or dendritic cell‐derived exosomes, with the idea that MHC–peptide complexes on the exosomal surface would stimulate an MHC‐restricted cancer‐specific immune response. This was also verified in mouse systems, whilst the effects in human clinical systems were more modest. Several studies have explored the mechanisms for exosomal T‐cell activation, and a picture emerges where the antigen‐presenting cells, possibly both B cells and dendritic cells of the recipient, are needed to induce a potent T‐cell response to exosomes. Therefore, the exosomes function more as an adjuvant‐like delivery system of antigens, and we need to further understand the exact components that trigger the most broad and potent immune responses. Here, we describe the grounds for using allogeneic exosomes for cancer therapy, something that would greatly improve the feasibility of new exosome‐based immunotherapeutic approaches to cure cancer. Abstract :